2022
DOI: 10.1049/cit2.12113
|View full text |Cite
|
Sign up to set email alerts
|

Automatic depression recognition by intelligent speech signal processing: A systematic survey

Abstract: Depression has become one of the most common mental illnesses in the world. For better prediction and diagnosis, methods of automatic depression recognition based on speech signal are constantly proposed and updated, with a transition from the early traditional methods based on hand-crafted features to the application of architectures of deep learning. This paper systematically and precisely outlines the most prominent and up-to-date research of automatic depression recognition by intelligent speech signal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…With the fast development of deep learning (DL), various approaches have recently been applied to SER with considerable performance gains [9][10][11][12]. In addition, other studies [13,14] have contributed to the research on the aforementioned challenges.…”
mentioning
confidence: 99%
“…With the fast development of deep learning (DL), various approaches have recently been applied to SER with considerable performance gains [9][10][11][12]. In addition, other studies [13,14] have contributed to the research on the aforementioned challenges.…”
mentioning
confidence: 99%
“…Some authors also conducted a review study on depression detection. For instance, Wu et al ( 2022 ) conducted a similar review study on depression detection using speech signals. While the authors reported that there has been a shift from exploring auditory features to deep model for speech depression recognition, they recommended overcoming depression detection challenges by collecting clinical information on depression to explore the core mechanism of speech in depression.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that combining multiple modalities for accurate and effective depression analysis is a possible trend in future research. While the review study by Wu et al ( 2022 ) is also on depression detection, the authors focus more on employing deep learning methods with speech signals for depression detection, a contrast to this review study, which focuses on machine learning and deep learning models using various types of datasets for depression detection. We also quite differently propose the feature fusion method for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been growing interest in using arti cial intelligence (AI) to detect depression from a combination of text and audio features and answers of the Patient Health Questionnaire-8 (PHQ-8) survey. A study by [2] used a combination of audio, text, and PHQ-8 features to develop a multimodal deep learning model that achieved high classi cation accuracy in detecting depression. There is ample evidence [3,5] for text-based approach and have achieved high performance in detecting depression.…”
Section: Introductionmentioning
confidence: 99%